Long Term Survival of Pseudomonas aeruginosa in Distilled Water and in Normal Saline - Mohammed F. Al- Marjani (Journal of Global Pharma Technology, 2019)
Pseudomonas aeruginosa is an important opportunistic pathogen primarily causing nosocomial infections in immunocompromised patients and is responsible for high mortality rates in burn centers, it can be isolated from hospitals, from the water in intensive care units, as well as sinks, basins, drains, showers, toilets and bathtubs, leading to transmission of P. aeruginosa infections. To determine the physiological adaptations which allow P.aeruginosa to survive in aqueous environments, we performed this experiment by transfer the bacterial cultures from Luria broth to distilled water and normal saline and incubate for 6 months and 12 months respectively. P. aeruginosa was able to survive in distilled water for at least 180 days( 6 months) and in normal saline for more than 360 days(12 months). We also examined the ability of this cells to pyocyanin production and antibiotic resistance, and the results showed that P. aeruginosa  cells were able to produce pyocyanin and resist to  cefotaxime , augmentin , ceftazidime cefepime and sensitive to imipenem , norfloxacin and gentamicin. The results of this study revealed that  P. aeruginosa bacteria can be preserved in distilled water or normal saline for several months, and able to pyocyanin production as well as antibiotic resistance. It is important to understand how this bacteria survives in water. Understanding the mechanisms of survival in water may contribute to novel solutions for the prevention of P. aeruginosa infection and transmission.Keywords: Persistance, Preservation, Saline, Water.